Dampak Pembangunan Jalan Tol Terhadap Produksi Pajale (Padi, Jagung, Kedelai) di Kecamatan Tanjung Kabupaten Brebes - Gias Agrianto; Etty Soesilowati (Journal of Economics and Business, 2020)
This study aims to determine: (1) Rice, Corn and Soybean production before and after the construction of the Kanci-Pejagan Toll Road in Tanjung District, Brebes Regency and (2) Productivity Rice, Corn and Soybean before and after the construction of the Road Kanci-Pejagan Toll Road in Tanjung District, Brebes Regency. The study was conducted in Tanjung Subdistrict, Brebes Regency. The study was conducted from January to March 2020. The research design used in this study is a quantitative study with a sample of 35 farmers affected by toll road construction. Data collection techniques were carried out by direct interviews with sample farmers, and for supporting data obtained from libraries and agencies / agencies related to the problem under study. To find out the difference between Rice, Corn, and Soybean production and productivity before and after the construction of the Kanci - Pejagan toll road, different test analysis was used. To test the hypotheses about differences in production and productivity before and after the construction of the toll road used hypothesis testing with the t test approach. The results showed that: (1) Kanci - Pejagan Toll Road Development had an impact on Production Rice, Corn, Soybean: (a) Rice production increased by 2.40 tons (2.05%) after toll road construction. Different test results showed no difference in rice production before and after the construction of the toll road, (b) Corn production decreased by 4.04 tons (-6.59%) after the construction of the toll road. Different test results showed that there were differences in corn production before and after the construction of the toll road, (c) Soybean production increased by 0.19 tons (1.95%), after the construction of the toll road. Different test results showed that there was no difference in soybean production before and after the construction of the toll road, and (2) the construction of the Kanci - Pejagan Toll Road had a significant impact on Productivity Rice, Corn, Soybean: (a) Rice productivity increased by 1.01 ton / ha (20.95%). Different test results showed there were differences in rice productivity before and after the construction of the toll road, (b) Maize productivity increased by 0.91 tons (12.36%). Different test results showed that there were differences in corn productivity before and after the construction of the toll road, (c) Soybean productivity increased by 0.42 tons (21.71%) .The different test results showed there were differences in soybean productivity before and after the construction of the toll road.